2023
DOI: 10.1021/acs.analchem.2c03953
|View full text |Cite
|
Sign up to set email alerts
|

Using the Synergy between HPLC-MS and MALDI-MS Imaging to Explore the Lipidomics of Clear Cell Renal Cell Carcinoma

Abstract: Lipid imaging mass spectrometry (LIMS) has been tested in several pathological contexts, demonstrating its ability to segregate and isolate lipid signatures in complex tissues, thanks to the technique's spatial resolution. However, it cannot yet compete with the superior identification power of high-performance liquid chromatography coupled to mass spectrometry (HPLC-MS), and therefore, very often, the latter is used to refine the assignment of the species detected by LIMS. Also, it is not clear if the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This finding indicates that single protoplast MALDI-FTICR-MS facilitates accurate and efficient high-throughput lipid measurement on single plant cells, positioning it as a valuable alternative to the LC-MS/MS approach. Similar results on the comparability and concordance between LC-MS and MALDI have also been recently reported in human cells (Martín-Saiz et al 2023). Moreover, our single cell measurements and data processing have the capacity to segregate the engineered and unengineered cell types within the 43-OWD group, demonstrating that based on single-cell heterogeneity, we can estimate which protoplasts have been genetically engineered (Supplementary Figure S5E).…”
Section: Resultssupporting
confidence: 87%
“…This finding indicates that single protoplast MALDI-FTICR-MS facilitates accurate and efficient high-throughput lipid measurement on single plant cells, positioning it as a valuable alternative to the LC-MS/MS approach. Similar results on the comparability and concordance between LC-MS and MALDI have also been recently reported in human cells (Martín-Saiz et al 2023). Moreover, our single cell measurements and data processing have the capacity to segregate the engineered and unengineered cell types within the 43-OWD group, demonstrating that based on single-cell heterogeneity, we can estimate which protoplasts have been genetically engineered (Supplementary Figure S5E).…”
Section: Resultssupporting
confidence: 87%
“…[155][156][157][158] A recent study by Martı ´n-Siaz and colleagues elegantly demonstrated the blending of MALDI-MSI and HPLC-MS to distinguish how well the two techniques correlate with one another in lipid biomarker discovery in clear cell renal cell carcinoma. 159 This study found that both MALDI-MSI and HPLC-MS experiments could spatially classify the lipid signature to distinct regions in the kidney, such as the cortex and medulla. A direct comparison of healthy vs. renal cell carcinoma was made using MALDI-MSI and quantification was conducted using internal standards with HPLC-MS analysis.…”
Section: Qmsi Of Lipidsmentioning
confidence: 78%
“…Thanks to the years of improvement in instrumentation and bioinformatics, MALDI-MSI was developed to a method capable of lipid classes and species identification and semi-quantification with no need to use chromatographic separation [76,85]; it is therefore considered as a universal tool for the study of lipids [76]. Evidence of the versatility of MALDI-MSI was recently proven by Martín-Saiz et al [86]. The authors used a combination of two independent methods, MALDI-MSI and HPLC-MS, for lipids screening in clear cell renal cell carcinoma patients.…”
Section: Mass Spectrometry Imagingmentioning
confidence: 99%